Aspirin Induces platelet apoptosis. (December 2013) - Zhao, Lili; Zhang, Weilin; Chen, Mengxing; Zhang, Jiansheng; Zhang, Mingyi; Dai, Kesheng
<x xml:space="preserve">Abstract</x> Aspirin is widely used in the treatment of a number of clinical conditions. Although aspirin is being thought to be a relatively "safe" medicine, it also has some side effects, particularly the risk of bleeding which may be severe and lead to death. The mechanisms, however, are not totally understood. It has been reported recently that aspirin induces apoptosis in many cell types. Thus, the aim of the current study is to explore whether aspirin induces platelet apoptosis. The data show that mitochondrial transmembrane potential (ΔΨm) depolarizations and phosphatidylserine (PS) exposures were dose-dependently induced by aspirin in platelets. To further confirm that aspirin incurs platelet apoptosis, caspase-3 activity was measured in platelets, and the result indicated that aspirin induced caspase-3 activation. Furthermore, the mean volume of platelets incubated with aspirin was obviously reduced. Caspase inhibitor z-VAD-fmk inhibited aspirin induced apoptotic platelet shrinkage and ΔΨm depolarization, but had no effect on PS exposure. In addition, platelets incubated with cyclooxygenase inhibitor indomethacin did not incur ΔΨm depolarazation and PS exposure. Taken together, the data indicate that aspirin induces platelet apoptosis via caspase-3 activation.